Stanowisko dyplomacji USA wobec kwestii bezpieczeństwa międzynarodowego na konferencji „wielkiej czwórki" w Genewie (18-23 VII 1955 r.) - Brykowska, Monika (Acta Universitatis Lodziensis. Folia Historica, 1997)
It was the problem of security that constitute the core of the dispute at the „Big Four” Conference in Geneva. That matter was considered in two main aspects: the question of the unification of Germany and that of disarmament. American delegation attached the main importance to the first problem. Eden’s plan proposing the unification of the two German states on the basis of free elections in the nearest possible time dominated the negotiations. According to the American the further prolongation of the division of Germany was an abnormal situation contradictory to the Potsdam agreements and threating the European security. As a matter of fact Washington aimed at the inclusion of the unified Germany into the military structures of NATO. On the other hand Kremlin being aware of the improbability of the unification of Germany by the extension of the Soviet influence to the FRG pointed up officially the remilitarization of West Germany as the main obstacle on the way to the unification of the country. According to the original American assumptions Geneva meeting should have merely drawn the public attention to the problem of international security. While Washington supported the balance of power system based as far as the West was concerned on the NATO, Moscow promoted the principle of the collective security. Regarding the disarmament problem the U.S.A. demanded the creation of the efficient control system. This resulted in the American „Open Skies” proposal. T hat idea was the first step to the development of the outer space means of the verification of the observation of agreements. The Geneva Summit offered the opportunity to disuss the most thorny European problems of the 1950s. From the American point of view it answered however none of the most interesting questions concerning the satellite slates of the U.S.S.R. and the international communist movement.